2016
DOI: 10.1002/adma.201602570
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Organic Solar Cells Based on Two Compatible Nonfullerene Acceptors with Power Conversion Efficiency >10%

Abstract: Two different nonfullerene acceptors and one copolymer are used to fabricate ternary organic solar cells (OSCs). The two acceptors show unique interactions that reduce crystallinity and form a homogeneous mixed phase in the blend film, leading to a high efficiency of ≈10.3%, the highest performance reported for nonfullerene ternary blends. This work provides a new approach to fabricate high-performance OSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
175
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 262 publications
(178 citation statements)
references
References 58 publications
1
175
1
1
Order By: Relevance
“…[1][2][3][4][5] Combined developments in material and device engineering mainly contributed to such rapid advances. [53] These two NFAs are miscible and formed a homogeneous mixed phase, resulting in superior device performance, which offers a new direction in device optimization. However, it should be realized that For example, we have recently reported that high-performance ternary OSCs can be fabricated with a twisted perylene diimide acceptor (SdiPBI-Se) and a fused-ring electron acceptor (ITIC-Th).…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Combined developments in material and device engineering mainly contributed to such rapid advances. [53] These two NFAs are miscible and formed a homogeneous mixed phase, resulting in superior device performance, which offers a new direction in device optimization. However, it should be realized that For example, we have recently reported that high-performance ternary OSCs can be fabricated with a twisted perylene diimide acceptor (SdiPBI-Se) and a fused-ring electron acceptor (ITIC-Th).…”
mentioning
confidence: 99%
“…[64,65] Concurrently, tuning composition of the ternary blend was found to give rise to a change in the energy of the charge transfer states, which is in turn directly related to V oc . [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] This subtle optimization point is also evident in the series of TSC devices studied here. On the other hand, V oc is also highly limited by the intrinsic nonradiative recombination losses, and this issue has recently been rigorously investigated for binary blend systems.…”
Section: Discussionmentioning
confidence: 87%
“…[16] The second polymer is poly[(5,6-difluoro-2,1,3-benzothiadiazol-4,7diyl)-alt-(3,3′″-di-(2nonyltridecyl)2,2′;5′,2″;5″,2′″-quaterthiophen-5,5′″-diyl)] (PffBT4T-C 9 C 13 ) with a quaterthiophene donor unit and a difluorobenzothiadiazole acceptor unit and it gives high efficiency in binary BHJ solar cells. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] This intriguing morphological changes are highly connected to the electrical properties and device FF. The LBG polymer has enabled the extension of absorption to 900 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Solution-processable small molecule (SM) alternatives to polymer donors are proving particularly promising in bulkheterojunction (BHJ) solar cells with fullerene [1][2][3][4][5] and nonfullerene [6][7][8][9][10][11][12] acceptors. With fullerenes (e.g., phenyl-C 61 -butyric acid methyl ester or its C 71 analog), BHJ solar cell efficiencies have progressed to >10% [13][14][15][16][17] and, while higher-mobility materials (>10 −3 cm 2 (V s) −1 ) with favorable self-assembly patterns and optimum thin-film morphologies are required to continue improving these efficiencies, the breadth of recent studies shows that material structure governs each one of those attributes.…”
Section: Introductionmentioning
confidence: 99%